Implementation and Role of Students in the Pancasila Student Profile Strengthening Project (P5) at SMPN 4 Gamping - Widyawati, Ani; Murniningsih, Murniningsih; Tussupbekova, Madina (Sekolah Pascasarjana Universitas Ibn Khaldun Bogor, 2025)
The Pancasila Student Profile Strengthening Project (P5) is an integral part of the Merdeka Curriculum, aimed at shaping Indonesian students to be individuals of noble character, independence, mutual cooperation, global diversity, critical thinking, and creativity. This article discusses the implementation of the P5 program at SMPN 4 Gamping and explores the active roles of university students in supporting the program. This study employs a descriptive qualitative method using observation, interviews, and documentation as data collection techniques. The findings reveal that university students act as facilitators, mentors, and inspirators in P5 activities, particularly in the development of environment-based, entrepreneurial, and cultural arts projects. Their involvement has shown a positive impact on students’ enthusiasm and participation, while also serving as a means for university students to enhance their social and pedagogical competencies. These findings emphasize the importance of synergy between higher education institutions and primary education units in supporting the implementation of the Merdeka Curriculum, especially through project-based learning activities like P5.